The Effect of Service Quality on Customer Satisfaction at PT. Securindo Packatama Indonesia in Tangerang - Jasmani, Jasmani (Management Science Doctoral Program, Pasundan University, 2023)
This study aims to determine the effect of service quality on customer satisfaction at PT. Securindo Packatama Indonesia in Tangerang. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable service quality obtained an average score of 3.41 with good criteria. The consumer satisfaction variable obtained an average score of 3.84 with good criteria. Service quality has a significant effect on customer satisfaction with the regression equation Y = 8.914 + 0.863X, and a correlation value of 0.787 or strong with a determination of 62.0%. The hypothesis test obtained a significance of 0.000 <0.05.